Pharmacists closing health disparity gaps through pharmacogenomics. Issue 8 (10th May 2022) - Formea, Christine M.; Schultz, April J.; Empey, Philip E.
Abstract: As the health care community recognizes the need to address health disparities, practitioners are working diligently to promote health equity. It is each of our responsibilities to identify and work to overcome barriers to equitable health care that our patients experience. Many factors contribute to health care disparities across the country, and because of this, health care providers must employ different strategies to resolve gaps in equity. Precision medicine and its constituent element of pharmacogenomics offer a unique opportunity to lead the way in serving patients as individuals with varying needs. Pharmacogenomics can be used as a solution for breaking down barriers including the lack of diversity in research, access for rural or underserved geographical locations, overcoming economic factors, improving education, and increasing technological portability. In this article, we review how clinical pharmacists using pharmacogenomics can play a key role in identifying and overcoming some of these barriers that lead to health care disparities.